2006
DOI: 10.1371/journal.ppat.0020107
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Membrane Proteomics Reveals New Cellular Targets of Viral Immune Modulators

Abstract: Immunomodulators of pathogens frequently affect multiple cellular targets, thus preventing recognition by different immune cells. For instance, the K5 modulator of immune recognition (MIR2) from Kaposi sarcoma-associated herpesvirus prevents activation of cytotoxic T cells, natural killer cells, and natural killer T cells by downregulating major histocompatibility complex (MHC) class I molecules, the MHC-like molecule CD1, the cell adhesion molecules ICAM-1 and PECAM, and the co-stimulatory molecule B7.2. K5 b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
217
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 195 publications
(232 citation statements)
references
References 63 publications
14
217
1
Order By: Relevance
“…Bst-2 expression was inducible by IFN treatment in 293T or HT1080 cells, consistent with the previous observation that cell lines that did not normally require Vpu for efficient virus release became Vpu-dependent upon IFN treatment (22). Although Vpu had no overt effects on ectopically expressed Bst-2 levels and cellular distribution (29), Vpu clearly downregulated cell surface expression of Bst-2 in 293T cells (23) and caused a reduction of endogenous Bst-2 expression in HeLa cells (30). Randomization of the Vpu TM domain abolished the ability of Vpu to overcome the inhibitory effects of Bst-2 on virus release (23), consistent with our previous data on the importance of the Vpu TM domain for this effect (17).…”
Section: Hiv-1 Vpu Enhances the Release Of Virions From Infected Cellssupporting
confidence: 89%
See 2 more Smart Citations
“…Bst-2 expression was inducible by IFN treatment in 293T or HT1080 cells, consistent with the previous observation that cell lines that did not normally require Vpu for efficient virus release became Vpu-dependent upon IFN treatment (22). Although Vpu had no overt effects on ectopically expressed Bst-2 levels and cellular distribution (29), Vpu clearly downregulated cell surface expression of Bst-2 in 293T cells (23) and caused a reduction of endogenous Bst-2 expression in HeLa cells (30). Randomization of the Vpu TM domain abolished the ability of Vpu to overcome the inhibitory effects of Bst-2 on virus release (23), consistent with our previous data on the importance of the Vpu TM domain for this effect (17).…”
Section: Hiv-1 Vpu Enhances the Release Of Virions From Infected Cellssupporting
confidence: 89%
“…1 A, lane 4). Of note, Bst-2 appears as multiple bands on the gel with estimated sizes of 25-35 kDa presumably because of glycosylation as reported (30). FACS analysis revealed low but detectable surface expression of Bst-2 in untreated 293T cells that was strongly up-regulated after IFN␣ treatment [supporting information (SI) Fig.…”
Section: Hiv-1 Vpu Enhances the Release Of Virions From Infected Cellsmentioning
confidence: 73%
See 1 more Smart Citation
“…Whereas MARCH1 downregulates all isotypes of MHC II but not MHC I, MARCH9 was shown by other groups to act on MHC I and only on the DQ isotype of MHC II (25,49). In our overexpression system, however, we found that MARCH9 was also active on HLA-DR. We reasoned that by introducing portions of MARCH1 of increasing length into MARCH9, one should be able to delineate functional regions.…”
Section: Dimerization Of March1 Depends On the Transmembrane Domainscontrasting
confidence: 69%
“…Ten mammalian MARCH gene products have been recognized, and the majority shares a similar structure, including an N-terminal C4HC3-type RING finger (RING-CH finger) and two or more C-terminal transmembrane spans (22,23). Several members of this novel E3 ubiquitin ligase family have been shown to ubiquitinate and down-regulate transmembrane proteins, such as major histocompatibility complex class I and II, B7-2, CD166, and ICAM-1 (24)(25)(26)(27)(28).…”
mentioning
confidence: 99%